Development of Logistics Technology: An Analysis based on the 4.0 Era - Shahparan, Mohammad; Klykov, Artem; Salnikova, Elena; Firdavsbek, Shokirov (PT. Riset Press International, 2024)
The paper explores the concept of the development of logistics technology based on 4.0 and how logistics is driven by technology. It aims to guide future research and assist managers in implementing the development of technology logistics 4.0 concepts. Qualitative methods are used in this paper. Data related to logistics technology was collected from different online sources. The evolution of logistics technology in the era of Industry 4.0 has been significant. Logistics 4.0, a concept emerging from Industry 4.0, focuses on the digital transformation of logistics management. Logistics technology like Artificial Intelligence, Machine Learning, and Big Data in logistics management to enhance and optimize processes and communication between different systems in logistics operations. The rapid advancement of Information Technology has played an essential role in promoting modern logistics information technologies.